Biomass production and nutrient use efficiency in white Guinea yam (Dioscorea rotundata Poir.) genotypes grown under contrasting soil mineral nutrient availability - Matsumoto, R.; Asfaw, A.; Ishikawa, H.; Takada, K.; Shiwachi, H.; Asiedu, R. (Frontiers Media, 2022)
Yam (Dioscorea spp.) is of great importance to food security, especially in West Africa. However, the loss of soil fertility due to dwindling fallow lands with indigenous nutrient supply poses a challenge for yam cultivation. This study aimed to determine shoot and tuber biomass and nutrient use efficiency of white Guinea yam (Dioscorea rotundata) grown under low- and high-NPK conditions. Six white Guinea yam genotypes were used in field experiments conducted at Ibadan, Nigeria. Experiments were conducted with low soil NPK conditions with zero fertilizer input and high soil NPK conditions with mineral fertilizer input. Differences in response to soil NPK conditions, nutrient uptake, and nutrient use efficiency (apparent nutrient recovery efficiency) were observed among the tested genotypes. The genotypes TDr1499 and TDr1649, with high soil fertility susceptibility index (SFSI>1) and an increase in shoot and tuber biomass with fertilizer input, were recognized as susceptible to soil NPK conditions. There was a marked difference in apparent nutrient recovery efficiency; however, there was no varietal difference in physiological efficiency. Differences in apparent nutrient recovery efficiency among genotypes affected the fertilizer response (or susceptibility to soil NPK conditions) and the nutrient uptake. In contrast, the genotype TDr2029, with SFSI<1 and low reduction in shoot and tuber production between non-F and +F conditions, was recognized as a less susceptible genotype to soil NPK status. It was revealed that NPK fertilization did not reduce tuber dry matter content, regardless of genotype differences in susceptibility to soil NPK conditions. Hence, this could be helpful to farmers because it implies that yield can be increased without reducing tuber quality through a balanced application of soil nutrients. Our results highlight genotypic variation in sensitivity to the soil NPK availability, nutrient uptake, and nutrient use efficiency white Guinea yam. Differences in susceptibility to soil NPK conditions could be due to the genotypic variations in nutrient recovery efficiency white Guinea yam. Our findings could contribute to breeding programs for the development of improved white Guinea yam varieties that enhance productivity in low soil fertility conditions with low and high-input farming systems.